Tensile strength of woven yarn kenaf fiber reinforced polyester composites - Ismail, Al Emran; Che Abdul Aziz, M.A. (Universiti Malaysia Pahang Publisher, 2015)
This paper presents the tensile strength of woven kenaf fiber reinforced polyester composites. The as-received yarn kenaf fiber is weaved and then aligned into specific fiber orientations before it is hardened with polyester resin. The composite plates are shaped according to the standard geometry and uni-axially loaded in order to investigate the tensile responses. Two important parameters are studied such as fiber orientations and number of layers. According to the results, it is shown that fiber orientations greatly affected the ultimate tensile strength but it is not for modulus of elasticity for both types of layers. It is estimated that the reductions of both ultimate tensile strength and Young’s modulus are in the range of 27.7-30.9% and 2.4-3.7% respectively, if the inclined fibers are used with respect to the principal axis.